Loneliness in couples and its relationship with attachment - Granillo-Velasco, Luisa Fernanda (Universidad Autónoma de Tamaulipas, 2020)
Loneliness is a phenomenon with important consequences in the life of those who suffer from it, including on their psychological health. This has been conceived as an unpleasant experience related to the need for unsatisfied interpersonal intimacy, which implies an imbalance in the level of socio-affective interaction of an individual and occurs when the individual’s social  network is deficient. Its measurement has been carried out through different instruments, among which the Social and Emotional Loneliness Scale for Adults (SELSA), which includes loneliness in 3 social domains: couple, family and friends, stand out for their psychometric characteristics. The objective of this research was the psychometric validation of the Social and Emotional Loneliness Scale for Adults (SELSA) in the context of the couple’s relationship, as well as assess its relationship with attachment styles in Mexico. This requires an accidental non-probabilistic sample of 194 heterosexual couples. The study design was instrumental because the validation of a new measure of loneliness was performed and correlated to the analysis of Pearson’s correlation between loneliness factors and attachment styles. As a result of the validation, 5 factors were obtained, accompaniment of friends, accompaniment of the partner, accompaniment of the family, feeling of emptiness and longing for which the last two had not been obtained in the original version. Finally, when analyzing the relationships between attachment styles and loneliness, interesting data were observed that indicate the importance of the accompaniment of the partner when secure attachment is developed. Furthermore, the data also show the central role played by the accompaniment of family and friends when anxious or avoidant attachments, in addition to higher rates of feelings of emptiness and longing, are experienced.